2017
DOI: 10.1080/02643294.2017.1394834
|View full text |Cite
|
Sign up to set email alerts
|

Non-fluent speech following stroke is caused by impaired efference copy

Abstract: Efference copy is a cognitive mechanism argued to be critical for initiating and monitoring speech: however, the extent to which breakdown of efference copy mechanisms impact speech production is unclear. This study examined the best mechanistic predictors of non-fluent speech among 88 stroke survivors. Objective speech fluency measures were subjected to a principal component analysis (PCA). The primary PCA factor was then entered into a multiple stepwise linear regression analysis as the dependent variable, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(4 citation statements)
references
References 49 publications
(88 reference statements)
0
4
0
Order By: Relevance
“…In the context of SE, previous work suggests damage to anterior or posterior language regions, or the connections between the 2, could negatively impact speech motor programming, which relies upon intact feedforward and feedback projections. 3,24 With regard to clinical disorders such as aphasia that result from brain injury, participants with non-fluent aphasia are hypothesized to have an impaired efference copy due to left IFG damage and subsequently, aberrant oscillatory function. To compensate for the absence of an efference copy, the literature suggests that an AV SE model provides an external efference copy by recruiting residual posterior regions (i.e., visual speech units in the pMTG) to induce more fluent speech production.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of SE, previous work suggests damage to anterior or posterior language regions, or the connections between the 2, could negatively impact speech motor programming, which relies upon intact feedforward and feedback projections. 3,24 With regard to clinical disorders such as aphasia that result from brain injury, participants with non-fluent aphasia are hypothesized to have an impaired efference copy due to left IFG damage and subsequently, aberrant oscillatory function. To compensate for the absence of an efference copy, the literature suggests that an AV SE model provides an external efference copy by recruiting residual posterior regions (i.e., visual speech units in the pMTG) to induce more fluent speech production.…”
Section: Discussionmentioning
confidence: 99%
“…Atypical entrainment to speech has been shown to play a role on various neuropsychological disorders such as dyslexia, stroke, and Broca's aphasia (Goswami, 2011;Molinaro et al, 2016;Feenaughty et al, 2017;Liberto et al, 2018;Thors, 2019;Lizarazu et al, 2021b,c). For example, in terms of developmental dyslexia, Goswami (2011) theorized that atypical speech-brain entrainment could be part of the underlying cause.…”
Section: Clinical Neurofeedback Applications Of Speech-brain Entrainmentmentioning
confidence: 99%
“…The focus of the present study is on post-stroke non-fluent aphasia (expressive or Broca's aphasia) that is frequently associated with lesions located within the left inferior frontal gyrus (Ardila et al, 2016;Van Der Meulen et al, 2016). Broca's aphasia is characterized by non-fluent spontaneous speech, apraxia of speech, agrammatism, anomia, effortful speech production, limited vocabulary access and short sentence production, while language comprehension remains relatively intact (Baqué et al, 2015;Cortese et al, 2015;Feenaughty et al, 2017). These deficits often include symptoms such as articulation errors or dysfluencies that are also typical of dysarthria or apraxia of speech.…”
Section: Introductionmentioning
confidence: 99%
“…These speech and language disturbances may be due to one or several impaired speech production processes, such as selection and planning of speech output, articulatory implementation of selected and planned speech segments, articulatory implementation of speech phonetic parameters and coordination of speech articulators (Kurowski, Hazen, & Blumstein, 2003;Nespoulous, Baqué, Rosas, Marczyk, & Estrada, 2013). Recent studies have shown that less fluent speech may be caused by the inability to create and use an efference copy (internal representation of the speech plan) for speech motor control (Feenaughty et al, 2017;Fridriksson et al, 2012Fridriksson et al, , 2015. For patients with aphasia following stroke, speech and language therapy has been shown to be beneficial in terms of improving language comprehension and production (Brady et al, 2016).…”
Section: Introductionmentioning
confidence: 99%